ChemInform Abstract: Regioselective Asymmetric Allylic Alkylation Reaction of α‐Cyanoacetates Catalyzed by a Heterobimetallic Platina‐/Palladacycle. Issue 21 (6th May 2016) - Weiss, Marcel; Holz, Julia; Peters, Rene
Abstract: The allylation of α‐cyanoacetates in the presence of a heterobimetallic Pt(II)/Pd(II) catalyst is studied.